Performance of gender- and age-specific cut-points versus NCEP pediatric cutpoints in dyslipidemia screening among Chinese children - Xiao, P.; Huang, T.; Y. Yan; X. Zhao; H. Li; Mi, J. (AtherosclerosisAtherosclerosisAtherosclerosis, 2018)
BACKGROUND AND AIMS: Considerable attention is given nowadays to the presence of cardiovascular diseases risk factors in children. The current blood lipid classification system for Chinese children was based on the United States National Cholesterol Education Program (NCEP) cutpoints, which did not take the age, gender and race differences into consideration. This study aimed to develop gender- and age-specific lipid cutpoints for dyslipidemia screening in Chinese children and compare the ability of new cutpoints and NCEP pediatric cutpoints to predict obesity and unfavorable blood pressure (BP) levels. METHODS: Data were obtained from a nationwide multicenter cross-sectional study: The China Child and Adolescent Cardiovascular Health Study, comprising 12,875 Chinese children aged 6-18 years. We calculated cutpoints for abnormal levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) that were linked to Chinese adult abnormal lipid thresholds using the General Additive Model for Location Scale and Shape method. RESULTS: Borderline-high and high cutpoints (TC, LDL-C and TG) as well as low cutpoints (HDL-C) were developed to classify the abnormal blood lipid levels in Chinese children. Better performance for prediction of obesity, elevated BP, and hypertension were found with the proposed cutpoints in comparison with the NCEP pediatric cutpoints (AUC for obesity: 0.612 vs. 0.597, p=0.017; AUC for elevated BP: 0.529 vs. 0.521, p=0.017; AUC for hypertension: 0.536 vs. 0.527, p=0.016). CONCLUSIONS: The gender- and age-specific cutpoints should improve the accuracy of dyslipidemia screening in China and be more reasonable in practice.